First UTI episode in life in infants <1 year of age: Epidemiologic, clinical, microbiologic and disease recurrence characteristics - Oana Falup-Pecurariu; Eugene Leibovitz; Cristiana Vorovenci; Raluca Lixandru; Flavia Rochman; Vlad Monescu; Ron Leibovitz; Laura Bleotu; Cristian Falup-Pecurariu (Elsevier, 2020)
Background: To examine the epidemiologic and microbiologic characteristics of first and recurrent UTI in young infants. Methods: A retrospective study of all infants <1 year hospitalized during 2014-2017 with their first UTI and followed during their first year of life. Results: 191 infants were enrolled; 69 (36.12%) patients were <2 months and 32 (16.8%) developed R-UTI during the follow-up. The five most common uropathogens were Escherichia coli, Klebsiella spp., Enterococcus spp., Proteus mirabilis and Staphylococcus aureus. High resistance rates were recorded for ampicillin, amoxicillin/clavulanic acid, TMP/SMX, cefuroxime, ceftriaxone, piperacillin/tazobactam and gentamicin among E. coli and Klebsiella spp.; 29.15% E. coli and 42.9% Klebsiella spp. were ESBL-positive. 53.2% of recurrent UTI (R-UTI) episodes were diagnosed within 2 months after the initial UTI episode. E. coli (40.6%) and Klebsiella spp. (37.55) were the most frequent R-UTI pathogens. Twenty-five (78.1%) R-UTIs were caused by recurrent uropathogens representing new infections. Antibiotic resistance rates at recurrence were similar to those at initial UTI, except for a significant increase in E. coli and Klebsiella spp. resistance to piperacillin/tazobactam. Conclusion: We reported high antibiotic resistance rates to major antibiotic classes used in UTI treatment. Most R-UTI episodes were caused by uropathogens different than those isolated at the initial UTI episode and were caused by highly-resistant organisms. Our findings require frequent monitoring and possible modification of the empiric and prophylactic antibiotic therapy protocols in use. As a result of our findings, the protocol for initial empiric treatment of infants with suspicion of UTI was modified by changing gentamicin to amikacin in the treatment of infants <2 months of life and amikacin monotherapy (intravenous or intramuscular) was introduced as first-line therapy for infants >2 months of life.